The role of light in the rearing of Clarias gariepinus larvae: Effects on behaviour, growth and survival - Marc-Christopher Hildebrand; Nina Hentrich; Harry Wilhelm Palm (Aquaculture Reports)
The growth performance and behavior activity of African catfish Clarias gariepinus (Burchell 1822) larvae were examined under different light regimes. Larvae (average weight 0.095 g / length 2.28 cm) were reared in 50 L aquaria at a stocking density of 12 fish/L and challenged with red, yellow or blue light. In a second experiment, larvae from the same batch were challenged with different yellow light intensities of 0.07, 23.00 or 70.00 (W/m²/nm). Performance parameters were determined by fish counts as well as measuring the initial and final body weight. Video recordings were applied in order to evaluate ethological parameters. African catfish larvae were affected by different light spectra as seen in the number of lesions and swimming activity-, escape- and air-breathing behavior, where the subgroups with red and yellow color differed from the blue treatment. The swimming- and air-breathing activity were positively affected under low light intensities. The number of lesions also decreased under minimal illumination. The performance indicators feeding conversion rate (FCR), special growth rate (SGR) or the final mean weight were not affected by any light treatment. Fish mortality and growth performance were not significantly influenced by the respective light treatment, we therefore recommend that yellow and dimmed light is most suitable for the initial rearing of African catfish larvae with respect to improved fish welfare.